Sistema de monitoramento da qualidade de água para piscicultura - Costa, Francisco Vinícius Lopes (Universidade Federal Rural do Semi-Árido, 2019)
The current growth of fish production has opened space for the insertion of technology in the productive means of this activity, such an opening arises with the purpose of increasing the profitability of the business. This project deals with the development of a prototype of hardware allied to a web system that aims to facilitate the activities of management, control and monitoring of production, through the variables temperature and pH, as well as provides means to automate the pump activation, drive of coolers and heaters and any other equipment. This work is justified by bringing novelties in the part of data visualization, which is using a web system, and also in its structure of data storage, which is a relational database. A bibliographic survey was carried out on the parameters of water quality, an analysis of work related to the automation of fish culture, and a study on which devices would be used to assemble the prototype. Finally, it was seen that the set (software + hardware) responded well to most of the tests and proved its usefulness as a tool for evaluating performance through graphs and tables.
Monografia
Keywords: Piscicultura; Pisciculture; Automação; Automation; pH; pH; Temperatura; Temperature; NodeMCU; NodeMCU; CIENCIAS EXATAS E DA TERRA::CIENCIA E TECNOLOGIA